Analisis Makna Fangowai dan Fame’e Afo pada Pesta Pernikahan Adat Nias Sebagai Bentuk Edukasi di Kota Gunungsitoli - Lesnawati Zendrato; Noveri Amal J Harefa (Indo-MathEdu Intellectuals Journal, 2023)
Culture is a lifestyle that grows and is owned by a group of individuals, then passed on to future generations. Each region in Indonesia has its own unique culture that is not shared by other regions. Local culture has an important role in shaping the identity of the Indonesian people. One aspect that needs to be considered and instilled is the customs in the wedding ceremony. Fangowai and fame'e afo are very significant elements in Nias traditional wedding ceremonies, the two of which cannot be separated from one another. Fangowai reflects respect for invited guests (fasumangeta) and shows high manners. The purpose of this research is to understand the meaning of fangowai and fame'e afo in the traditional Nias wedding tradition in Gunungsitoli City, as well as learn lessons that can be applied in everyday life. The research method used is a qualitative approach with a descriptive research type. Based on the results of the study, it can be concluded that the meaning of fangowai and fame'e afo at the traditional Nias wedding in Gunungsitoli City are as the main and first tribute at the wedding, as sia'a böwö (eldest custom), as Nias traditional cultural heritage